Testing the performance of rival warehousing policies through discrete event simulation - Vilas-Boas, J. (2016)
This research tested the performance of alternative warehouse designs concerning the picking process. The chosen performance measures were Travel Distance and Total Fulfilment Time. An explanatory case study was built up around a model implemented with SIMUL8. Hypotheses were set by selecting outcomes from the literature survey matching popular empirical findings. 17.4% reductions were found for Total Fulfilment Time and Resource Utilisation. The latter was then used as a proxy for operational efficiency. Literal replication of theoretical data-patterns was considered as an internal validity sign. Assessing the estimated changes benefits ahead of implementation was found to be a contribution to practice.